2017
DOI: 10.3892/etm.2017.5595
|View full text |Cite
|
Sign up to set email alerts
|

JNK and NF‑κB signaling pathways are involved in cytokine changes in patients with congenital heart disease prior to and after transcatheter closure

Abstract: Congenital heart disease (CHD) is a problem in the structure of the heart that is present at birth. Due to advances in interventional cardiology, CHD may currently be without surgery. The present study aimed to explore the molecular mechanism underlying CHD. A total of 200 cases of CHD treated by transcatheter closure as well as 200 controls were retrospectively assessed. Serum cytokines prior to and after treatment were assessed by reverse-transcription quantitative polymerase chain reaction analysis. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…When considering VUS, we identified three candidate genes: MAPK8 , PDE1 , and ITGAE . It has been suggested that MAPK8 has a role in the pathogenesis of CHD . There is evidence from animal studies to suggest that PDE1 has important roles in cardiac defects such as hypertrophy and heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering VUS, we identified three candidate genes: MAPK8 , PDE1 , and ITGAE . It has been suggested that MAPK8 has a role in the pathogenesis of CHD . There is evidence from animal studies to suggest that PDE1 has important roles in cardiac defects such as hypertrophy and heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that MAPK8 has a role in the pathogenesis of CHD. 21 There is evidence from animal studies to suggest that PDE1 has important roles in cardiac defects such as hypertrophy and heart failure. The use of phosphodiesterase inhibitors in the treatment of heart failure has been considered.…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…Aside the systemic increase in serum pro-inflamatory cytokines, an increase in the myocardial synthesis of pro-inflammatory cytokines (IL-1b, IL-6, TNF-α), but also of IL-10 (predicted to be targeted by miR-99a), has been reported in euploid children with congenital cardiac defects, presumably an effect of pressure overload and correlate with serum levels [63]. Although most of the data point towards a hemodynamic overload of the DS hearts with septal defects as the cause of these changes, recent research has identified two major signaling hubs, JNK and NF-kB able to transduce cytokine signaling in the vertebrate myocardium and having a significant ethiopathogenic potential in children with congenital heart defects [64]. Experimental alteration of NF-kB in the cardiac primordium significantly alters the development of the outflow tract (the transient embryonic structure that connects the aortic sac with the ventricles and whose dismorphogenesis leads to conotruncal congenital heart defects) [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…CHD patients have shown the presence of circulating markers, primarily cytokines. Fan et al reported the observation of immune activation in patients with CHD, which was evident through an elevation in inflammatory cytokines and a reduction in anti‐inflammatory cytokines [ 66 ]. These cytokine levels returned to normal following transcatheter CHD treatment [ 66 ].…”
Section: Chd Gut Microbiome and Immunitymentioning
confidence: 99%